INTERRELATION BETWEEN LUNGS FUNCTiONAL PARAMETERS AND CONDiTiON OF BONE TISSUE AT THE TERMINAL PULMONARY PATHOLOGY - L. G. Ugay; E. A. Kochetkova; K. A. Burya; S. A. Albavichus (Acta Biomedica Scientifica, 2012)
The aim of this study was to evaluate the condition of mineral density of bone tissue at the terminal pulmonary pathology, to determine correlations between lungs functional parameters and. pre-transplantation bone mass. Materials and methods: we realized retrospective analysis of 74 case histories of patients with terminal pulmonary pathology, waiting for lung transplantation. MDBT in lumbar segment of spine (L2—L4) and. femoral neck (FN) was evaluated, with help of double-energy X-ray absorptiometry (Hologic). Function of external respiration was researched, gasometry and 6-minutes walking test were realized, in all the patients. Results: osteopenic syndrome in any zone of interest was registered in 69 % of patients. Normal indices of MDBT both in L2—L4 and. in FN were registered only in 11 % of patients. On our data the indices of T-criterion (both, in L2—L4 and. in FN) had. direct relation with, body weight index (BWI) and. total fatty mass. Direct correlation between MDBT, volume of forced expiration for 1 second. (FEV) (r = 0,49, p < 0,05 in L2—L4 and. r = 0,52, p < 0,05 in FN) and. indirect correlation with, total lungs capacity (TLC) (r = —0,53, p < 0,01) with residual lungs volume (RV) (r = —0,48, p < 0,05) only in FN. We revealed, reliable negative interrelation, of MDBT only with pCO2 of arterial blood (r = —0,54, p < 0,01 in L2—L4 and r = —0,48, p < 0,05 in FN). There were no reliable correlation between DLCO, 6-minutes walking test and. MDBT both in L2—L4 and. in FN. 11% of patients had. atraumatic fractures of different localization. Conclusion: thus, osteoporosis is sufficiently frequent system, manifestation, in patients with, different terminal pulmonary pathology in pre-transplantation period. Worsening of lungs functional parameters, low BWI and. decrease of total fatty mass can be strong predictors of osteoporosis at the serious respiratory pathology.